TRANSFORMASI KEPEMIMPINAN PERGURUAN TINGGI DAN JEJARING INTERNASIONAL - Bashori, Bashori; Vadhilla, Syukra (UIN Imam Bonjol Padang, 2019)
The issue of leadership becomes the study that never ends in every period. The leader is not only limited to being able to lead an organization, but the expected leader is a leader who is able to innovate and transform in finding solutions and developing a better organization. If quoting McGregor Burns' opinion, transformational leadership is a process in which leaders and followers together increase and develop their morality and motivation. In addition, a very brief but concise function that has been stated by the father of our education, Ki Hajar Dewantara, that a good leader must carry out functions, namely: